Impacto del covid-19 en el mercado laboral y los niveles de pobreza, 2017-2021 Ecuador. - Cartuche Nagua, Leonardo Jesus; Villavicencio Mateo, Kerly Rosaura (Universidad Técnica de Machala, 2022)
The labor market and poverty levels in Ecuador are very important issues, since they are indicators that are related to the development and growth of the country. The present case analysis addresses as a topic the IMPACT OF COVID-19 ON THE LABOR MARKET AND POVERTY LEVELS, 2017-2021 period covering a change from before the beginning of the pandemic and during its course in Ecuador. This work is important because it detailed data that proves the negative effect presented in the economic, social and health sector. The main objective of the study is oriented to: To know the variations that were registered in the labor market and in the levels of poverty from pre-pandemia to the presence of COVID-19 through the analysis of variables with the purpose of being able to determine its impact. The methodology used in the research is descriptive with a mixed approach (quantitative and qualitative), it also presents documentary characteristics with the method of bibliographic review supported by data obtained from official sources such as: National Institute of Statistics and Census (INEC), Central Bank of Ecuador (BCE), World Bank (WB) and other theoretical sources that contribute and support the development of the topic to be investigated. The results of the research demonstrate that the unemployment and poverty variables show a severe increase with respect to the years prior to the global pandemic.
El mercado laboral y los niveles de pobreza en el Ecuador son temas muy importantes, puesto que son indicadores que están relacionados con el desarrollo y el crecimiento del país. El presente análisis de caso aborda como tema el IMPACTO DEL COVID-19 EN EL MERCADO LABORAL Y EN LOS NIVELES DE POBREZA, 2017-2021 periodo que abarca un cambio desde antes del inicio de la pandemia y durante su trascurso en el Ecuador. Este trabajo es importante porque se detalló datos que comprueban el efecto negativo presentado en el sector económico, social y sanitario. El objetivo principal del estudio se orienta en: Conocer las variaciones que se registraron en el mercado laboral y en los niveles de pobreza desde la prepandemia hasta la presencia del COVID-19 mediante el análisis de variables con la finalidad de poder determinar su impacto. La metodología empleada en la investigación es descriptiva con un enfoque mixto (cuantitativo y cualitativo), además presenta característica documental con el método de revisión bibliográfica sustentado los datos que se obtuvieron de fuentes oficiales como: Instituto Nacional de Estadísticas y Censos (INEC), Banco Central del Ecuador (BCE), Banco Mundial (BM) y otras fuentes teóricas que aportan y avalan el desarrollo de tema a indagar. Los resultados de la investigación permiten demostrar que las variables desempleo y pobreza presentan un acrecentamiento severo con respecto a los años anteriores a la pandemia mundial.
Keywords: ECUADOR; COVID-19; DESEMPLEO; POBREZA